Investigation of novel genes and functional roles in MEFV negative FMF patients through next-generation sequencing - Önen Özkılıç, Merve (Lisansüstü Eğitim Enstitüsü, 2023)
The p.Arg228Cys variant and the known pathogenic variant p.A230T are both located on the F-BAR domain, which is important for PSTPIP1 protein to form the functional trimeric complex with pyrin. The computational analyses of the xxi PSTPIP1 structure suggest that the p.Arg228Cys variant may cause a potential destabilization and change in the weak interaction network, leading to a stronger preference for certain interaction partners such as pyrin. Studies have shown that the p.Arg228Cys variant may lead to increased interaction with pyrin and reduced interaction with LYP phosphatase, which is normally required for the regulation of immune responses. The differences in symptoms between patients with the p.A230T or p.E250Q pathgoenic variants causing PAPA syndrome and patients with the p.Arg228Cys variant causing milder autoinflammatory symptoms in the patients in this study may be due to the diverse interaction strength of PSTPIP1 with different phosphatase proteins and pyrin protein. Within the scope of this thesis, it is found that p.Arg228Cys variant appears to increase the binding of PSTPIP1 to pyrin in PBMC samples of the patients. This was indicated by the higher levels of pyrin observed in the IP:PSTPIP1 lanes of our patient samples when compared to healthy controls. The interaction between PSTPIP1 and pyrin was increased in the patients as for P-III-2 1.43 fold and for P-II-1 patient 1.69 fold than HC1, and as for P-III-1 11.7 fold and for P-I-1 14.7 fold than HC2. This increased interaction may lead to hyperphosphorylation of PSTPIP1 and triggering the activation of pyrin inflammasome. Thus, the inflammation model in cultured PBMCs showed increased protein expression levels of pyrin, PSTPIP1, caspase-1, and IL1ß in cell lysates of patients with the p.Arg228Cys variant compared to the patient with a different heterozygote variant (p.A372V) and healthy control in the inflammation-induced condition (LPS+ATP) and secreted caspase1 and IL1ß levels were also found higher in supernatants of patients with p.Arg228Cys variant according to others in the inflammation-induced condition (LPS+ATP). Thus, it is important that other inflammation-related genes involvement should be considered in patients presenting with FMF phenotype negative for MEFV exon 10 recessive mutations. The targeted sequencing approach is useful for detecting rare pathogenic variations in patients with autoinflammatory phenotypes. Further functional analyses of the identified pathogenic variants could be helpful for better understanding the underlying molecular mechanism of FMF development.
MEFV negatif ailesel Akdeniz ateşi hastalarında yeni nesil dizileme yöntemiyle özgün genlerin ve işlevlerinin araştırılması
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2023
Keywords: genetics; genetik; disease; hastalık; molecular biology; moleküler biyoloji